Studies on the Relationship Between Chromium(III) ion and Thyroid Peroxidase Activity in Sera of Patients with Thyroid Dysfunction - Hasan, H. G.; Mahmood, T. J.; Ismael, P. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  objective of this study was to determine the concentration of trace element chromium(III) and thyroid peroxidase activity in human serum , and    to find a relationship between the concentration of chromium(III) and thyroid peroxidase activity in serum of patients with hypothyroidism, hyperthyroidism and healthy subjects. Serum thyroid peroxidase was measured by enzyme linked radioimmunoassay(ELISA) method and chromium determination was by atomic absorption spectrophotometer .Comparing the values of chromium concentration and thyroid peroxidase activity in both samples showed that there were significant positive correlations between chromium levels and thyroid peroxidase activity(P